MOLECULAR AND MORPHOLOGICAL INDICATORS (QUTHA ) Cucumis melo PLANTED IN IRAQ - & et al., Al- juboori (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field experiment was carried out at the Department of Horticulture and Landscape Gardening, College of Agricultural Engineering Sciences, University of Baghdad .during 2016. to investigate  the genetic diversity for six genotype of snake melon Cucumis melo var. flexuosus  (Qutha ), cultivated in Iraq. These selected genotypes were collected from Iraq's Governorates (Baghdad, Sulaymaniyah, Mosul, Salahadeein, and Diyala )in addition to commercial genotype and designated as A,B,C,D,E, and F, respectively. The treatments were arranged in randomized complete block design (RCBD) with three replications Genetic diversity among the six selected genotype was studied utilizing the random amplification of polymorphic DNA (RAPD) markers and linked with fruits morphological traits. The results  showed that the highest genetic diversity (0.285) observed between the genotype (A and B ) and  between (A and D) was (0.235) ,while the genotype (C and D) had the lowest genetic distances  which was  (0.031), as well as between( E and F) was (0.059).  Also the results revealed that Genetic distances depend on the variance phenotypic of fruits  recorded  about  (1 ) as highest number among the genotype  (A and D) , (B and D ), (C and D ), (D and E ), and (D and F ), while the lowest was about ( 0.091 ) for (A and C.)Genotype